Level of Satisfaction of Rice Farmers with the Performance of Agricultural Extension Workers in the Village of Dusun Baru Tabir District Merangin Regency - Asminar Asminar; Abu Bakar; Evo Afrianto; Setiono Setiono; Akhyarnis Febrialdi (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2025)
This study aims to determine the level of satisfaction of rice farmers with the performance of agricultural extension workers in Dusun Baru Village, Tabir District, Merangin Regency. The background of this study is the importance of agricultural extension workers as facilitators, educators, and liaisons between technological innovations and farmers, with direct implications for the success of agricultural development. The research was conducted from April 20 to May 20, 2021, using a quantitative survey method. Primary data were collected through interviews with questionnaires from 116 respondents selected via proportional random sampling from 18 farmer groups, totaling 582 people. Secondary data were obtained from the Tabir Subdistrict Agricultural Extension Center (BPP) and relevant literature. Data analysis was performed using a Likert-scale scoring technique, then interpreted using frequency distributions and mean values. The results showed that farmers' satisfaction with extension workers' performance was in the fairly satisfied category, with an average score of 2.02. In terms of social action and extension program planning, farmers rated their satisfaction as fairly satisfied (2.06), while extension implementation, technical expertise application, and extension worker performance scored 1.96, 2.02, and 2.02, respectively. Meanwhile, farmers' expectations of extension programs were also in the fairly satisfied category with an average score of 2.12. The interpersonal relationship indicator scored 2.17, and organizational management scored 2.07. These findings indicate that although farmers are reasonably satisfied with the performance of extension workers, there is still room for improvement, particularly in the implementation of extension services, strengthening farmer group institutions, and improving access to information and technology.